Characterisation of calcium carbonate formed by Bacillus Sphaericus via fermentation of urea - Azmi, Muhammad Syazwan; Teng, Siaw Lin; Tajarudin, Husnul Azan; Makhtar, Muaz Mohd Zaini; Daud, Zawawi (UTHM Publisher, 2018)
Microbiologically induced calcium carbonate precipitation (MICCP) has emerged as rather promising green technology compares to conventional calcium carbonate process. Bacillus sphaericus LMG22557 is a superior MICCP-capable microorganism that can potentially utilise urea from diverse sources. This study focuses on maximising and characterising the calcium carbonate produced from fermentation of synthetic urea and waste urea from chicken manure. Morphologies of calcium carbonate attributed from fermentation of urea and precipitation by different calcium source were studied by microscopic observation, Fourier-Transform Infrared (FTIR) and X-Ray Diffraction (XRD). Precipitation from calcium chloride produced more vaterite while precipitation from calcium nitrate tetrahydrate produced pure calcite. Higher specific yield productivity (0.2502 mol/g cell/h) was achieved with 200 rpm and 40 g/L urea concentration. The growth of B. sphaericus in chicken manure solution was achievable but with very low yield of bicarbonate ions (less than 0.0008 mol/g cells/h). In brief, B. sphaericus is able to produce calcium carbonate from synthetic urea while further study is required for chicken manure to be used as substitute.